Fully solution-processed, light-weight, and ultraflexible organic solar cells - Güler, Ezgi; Distler, Andreas; Basu, Robin; Brabec, Christoph; Egelhaaf, Hans-Joachim (Flexible and Printed Electronics, 2022)
Organic photovoltaic (OPV) devices have the potential to be superior to other PV technologies for the use in applications that require very high flexibility or maximum specific power (power-per-weight ratio), such as textile integration, wearable electronics, or outer space applications. However, OPV devices also require encapsulation by barrier films to reduce the degradation driven by extrinsic factors, which in turn limits their flexibility and leads to lower specific power values. In this work, fully solution-processed (including both electrodes) semitransparent organic solar cells (OSCs) with performance comparable with conventional indium tin oxide-based devices are processed directly onto different barrier films of varying thicknesses. Direct cell fabrication onto barrier films leads to the elimination of the additional polyethylene terephthalate substrate and one of the two adhesive layers in the final stack of an encapsulated OPV device by replacing the industrial state-of-the-art sandwich encapsulation with a top-only encapsulation process, which yields significantly thinner and lighter 'product-relevant' PV devices. In addition to the increase of the specific power to 0.38 W g(-1), which is more than four times higher than sandwich-encapsulated devices, these novel OSCs exhibit better flexibility and survive 5000 bending cycles with 4.5 mm bending radius. Moreover, the devices show comparable stability as conventionally encapsulated devices under constant illumination (1 sun) in ambient air for 1000 h. Finally, degradation under damp heat conditions (65 degrees C, 85% rh) was investigated and found to be determined by a combination of different factors, namely (UV) light soaking, intrinsic barrier properties, and potential damaging of the barriers during (laser) processing.
CRIS-Team WoS Importer:2022-05-13
Keywords: solution-processability; specific power; organic photovoltaics; silver nanowire; transparent electrodes; flexible electronics; barrier films